KOMPARASI PRINSIP VERIFIKASI POSITIVISME LOGIS DAN PENERAPAN HUKUM QIYAS - M. Marovida Aziz (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2021)
Abstract The view of the logical positivism group regarding science is based on the development of exact sciences, scientific truth can be measured positively, namely the truth must be real, concrete, logical, accurate and useful, but the effect behind everything abstract and metaphysical in the dimensions of life is ignored and regardless of observation. The main idea of logical positivism that was promoted by Alfred Jules Ayer, one of which is the principle of verification. In the application of the verification principle, it can also be taken for study studies in the determination of Qiyas law, namely by analogizing a law that has not yet been stipulated in the text, by testing and observing by verifying the causes of its similarity with the established law, determining the similarity of causes with logical parameters. and also empirical. The analogy in Qiyas must go through a verification stage, namely because it must be a real and visible nature by the five senses, and logic, as well as through the empirical proof stage. According to logical positivism and qiyas, the main condition is that it must be something that is visible, and get rid of pseudo-problems. Keywords: Logical positivism, Verification, Qiyas.